Gaharu Leaf Water Extract Reduce MDA and 8-OHdG Levels and Increase Activities SOD and Catalase in Wistar Rats Provided Maximum Physical Activity - Parwata, I Made Oka Adi; Manuaba, Ida Bagus Putra; Sutirtayasa, I Wayan Putu; Wita, I Wayan (BALI MEDICAL JOURNAL, 2016)
Background: Oxidative stress occurs due to an imbalance of the number of free radicals by the number of endogenous antioxidant produced by the body i.e. Superoxide Dismutase (SOD), Gluthathione Peroxidase (GPx), and Catalase. The imbalance between the number of free radicals and antioxida nts can be overcome with the end ogenous antioxidant intake that exogenous oxidative stress can be reduced. O ne of exogenous antioxidants is natural Gaharu leaf water extract. Objective: This research focus on the effect of Gaharu leaf water extract in reducing MDA and 8- OHdG and increase the activity of SOD and Catalase. Methods: This study was an experimental with post only controls group design. Experiment was divided into 5 groups of w istar rats, each consisting of 5 animals, i.e. negative control group without extract [K (-)], treatment 1 treated 50 mg/ kg BW/day of the extract (T1), treatment 2 treated 10 0 mg/ kg BW/day of the extract (T2), treatment 3 treated 200 mg/ kg BW/day of the extract (T3), and positive control group [K (+)] treated with vitamin Cat a dose 50 mg/ kg BW/day. All groups treated for 10 weeks. Every day, before treatment, each group was given a maximum swimming activity for 1.5 hours for 10 weeks. ELISA was used to measure MDA, 8-OHdG, SOD , and C atalase activities . Result: The research results showed that treatment of extract of leaves of Gaharu with an higher dose from 50 mg/kg BW up to 200 mg/ kg BW significantly decline (p <0.05) levels of MDA with the average ranging from 6.37±0.23, 5,56±0.27 and 4.32±0.27, 8-OHdG with a mean of 1.64±0.11, 1.26±0.46 , and 1.09±0.17. On the other hand the treatment also increase SOD activity with less ranging from 12.15±1.04, 15.70±2.02 , and 18.84±1.51, and Catalase ranging from 6,68±0.63, 8.20±1.14 and 9.29±0,79 in the blood of Wistar rats were given a maximum activity compared to the negative control group. This is probably higher phenol compounds (bioflavonoids) quantity content of the extract. These compounds synergistically affect their activity through capture and neutralize the free radicals that oxidized the lipid to less that automatically MDA production as the end result of oxidation lipid levels down, 8-OHdG down, the activity of SOD and Catalase ride. C onclusion: Gaharu leaf water extract reduced oxidative stress of Wistar rats through reduction of MDA and 8-O h dG mechanism. On the other hand, the extract increases SOD and Catalase activity.
Keywords: Gaharu leaf water extract, SOD, MDA, 8-OHdG and Catalase